Contribution to the study of the pancreatic, duct system in horses (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1973)
The study of the pancreas in 30 equities (15 males and 15 females) revealed that the Wirsung duct always proceeds from the union of two roots and they drain, separately, (93.3%) the right and the left lobes of the gland, seldom (6.7%) the collector of the right lobe also strains the posterior portion of the left lobe throughout its trajectory the Wirsung duel receives, as well as their roots, varied number of affluents. The Santorini duct, being present for the most part of the dissections (96.7%) reaches almost always (90.0%) the lesser duodenal papilla. Frequently (93.3%) connected with the Wirsung duct system, it opens itself, by its central, extremity directly in that duct (76.6%), in the duct of the left lobe (10.0%), in the border between them (3.3%;), or in the excretory canal of the right lobe (3.3%). The Santorini duct may appear free from tributaries (2) (26.7%) or to receive several afferents (70%).In a good deal of glands (5 6% ) we take notice of delicate anastomosis at the place of the bridge and they set up between both the collectors of the two lobes, right and left. It may appear, in other glandular regions, duct of appreciable caliber, communicating sometimes (6.7%) the distal portion of the mentioned collectors or even different sectors of the own drain duct of the right lobe.